2009
DOI: 10.3855/jidc.592
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemokines and soluble adhesion molecules in cytomegalovirus-positive renal transplant recipients

Abstract: Background: The relationship among cytomegalovirus (CMV) infection and the serum level of chemokines and soluble adhesion molecules is not well studied. This study aimed to assess chemokines and soluble adhesion molecules in CMV-positive Saudi renal transplant recipients. Methodology: The study was conducted in a tertiary hospital in Eastern Saudi Arabia over a 12-month period. All kidney transplant recipients who regularly attended the nephrology clinics were included (n = 150). Randomly selected age-and sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…However, a recent study conducted in Libya, another African country, reported 61% IgG and 5% IgM antibodies in pregnant women (Elnifro et al 2009). Generally, the presence of IgG antibodies is indicative of past exposure to an antigen (prevalence), whereas IgM antibodies represent recent infection with an agent (Obeid & Alzahrani 2010).…”
mentioning
confidence: 99%
“…However, a recent study conducted in Libya, another African country, reported 61% IgG and 5% IgM antibodies in pregnant women (Elnifro et al 2009). Generally, the presence of IgG antibodies is indicative of past exposure to an antigen (prevalence), whereas IgM antibodies represent recent infection with an agent (Obeid & Alzahrani 2010).…”
mentioning
confidence: 99%